Hybrid Digital Parenting Models: Integrating Social Cognitive Theory with Islamic Values in Early Childhood Development - Astuti, Ria; Aziz, Thorik; Yuniatari (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This research aims to develop a hybrid parenting model that integrates Bandura's Social Cognitive Theory with Islamic values to enhance early childhood development in the digital era. The shift in parenting due to technological advances has created challenges for Muslim families in maintaining spiritual identity while adapting to modern media. Through a phenomenological approach, data was collected via in-depth interviews, non-participant observation, and documentation from 15 Muslim families in Graha Kencana Residence, Pamekasan, Madura. The study identifies three hybrid parenting models: authoritarian-hybrid, democratic-hybrid, and permissive-hybrid. These models integrate Bandura’s four stages of observational learning (attention, retention, reproduction, motivation) with Islamic parenting methods (Al-Mukalatah, Al-I'tiyad, and Al-Ta'allum). The results demonstrate that parents can use technology to model positive behavior, helping children adapt to digital media while preserving religious values. This research provides a practical framework for Muslim families to effectively navigate the digital age, balancing technological engagement with religious teachings. It contributes to the field by offering a culturally relevant and spiritually grounded parenting model, which can be adapted by Muslim families worldwide to foster both digital literacy and moral integrity in children.